Produção de repolho em função de doses e fontes de potássio em cobertura - Correa, Carla Veronica [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP]; Rodrigues Claudio, Marina de Toledo [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The objective of this research was to evaluate the effects of rates and sources of potassium in top dressing on yield of cabbage hybrid Kenzan. Two experiments were conducted (15/07 to 22/11/2010 and 28/09/2010 to 27/01/2011) and nine treatments, resulted from a factorial 4 rates (45; 90; 135 and 180 kg ha(-1) of K2O) x 2 sources (KCl and K2SO4) + 1 control (without K in top dressing) were evaluated at randomized block design, with 4 replicates. After the harvest, fresh and dry weight of cabbage head and of external leaves; leaf number (from cabbage and external); diameter and height of cabbage head were evaluated. It was evaluated soil chemical characteristics at the end of first experiment and content of macro and micronutrients in plants. It was observed that potassium rates and sources did not influence most of evaluated characteristics. K content in plant increased linearly with KCl application. Results obtained show that, probably, it is not necessary application of K in top dressing when base fertilization is done with this nutrient, besides existing recommendations for this crop.
Yield of cabbage depending on rates and sources of potassium in top dressing
Keywords: Brassica oleraceae var. capitata; chloride; sulfate